2017
DOI: 10.1016/j.aninu.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fractionation of certain conventional- and lesser-known by-products for ruminants

Abstract: Dietary proteins for ruminants are fractionated according to solubility, degradability and digestibility. In the present experiment, 11 vegetable protein meals and cakes used in ruminant nutrition were included with a main focus on determining various nitrogen (N) fractions in vitro. Total N (N × 6.25) content varied from 22.98% (mahua cake) to 65.16% (maize gluten meal), respectively. Guar meal korma contained the lowest and rice gluten meal had the highest acid detergent insoluble nitrogen (ADIN; N × 6.25). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
1
5
0
1
Order By: Relevance
“…Due to its high acid detergent insoluble protein content linked to lignin and due to Maillard reaction products originated during roasting [56], HS is characterized by low rumen degradability. In fact, acid detergent insoluble protein is undegradable in the rumen and not digested by proteolytic enzymes in the small intestine, being therefore unavailable for protein synthesis [57]. The chemical analysis conducted on the HS used in our trial confirmed that the CP in HS (62 g/kg DM) is mostly undegradable inside the rumen (RDP = 5.0 g/kg DM CP).…”
Section: Dry Matter Intake Milk Yield and Milk Main Constituentssupporting
confidence: 52%
“…Due to its high acid detergent insoluble protein content linked to lignin and due to Maillard reaction products originated during roasting [56], HS is characterized by low rumen degradability. In fact, acid detergent insoluble protein is undegradable in the rumen and not digested by proteolytic enzymes in the small intestine, being therefore unavailable for protein synthesis [57]. The chemical analysis conducted on the HS used in our trial confirmed that the CP in HS (62 g/kg DM) is mostly undegradable inside the rumen (RDP = 5.0 g/kg DM CP).…”
Section: Dry Matter Intake Milk Yield and Milk Main Constituentssupporting
confidence: 52%
“…The protein that is soluble in phosphate-borate is known as a soluble protein, and it is assumed to degrade quickly in the rumen. This fraction is primarily composed primarily of non-protein compounds, such as ammoniacal nitrogen, urea, nitrates, amino-acids, small peptides, and true protein (Mohamed and Chaudhry 2008;Mahesh et al 2017). Urrego et al (2013) evaluated the composition of the nitrogenated compound of the residue of a crop of Agaricus bisporus from a Colombian company that used rice husks, sugarcane bagasse, poultry litter, and cotton as culture bed.…”
Section: Resultsmentioning
confidence: 99%
“…Although ADIN can be partially digestible (Wang et al, 2015), this fraction is accepted as the nitrogen that is nutritionally unavailable to ruminants and its negative correlation with dietary nitrogen digestibility. These values can be influenced by the plant's physiological maturity stage during harvest and its lignification (Moura et al, 2016) and heat damage (Mahesh, Thakur, Kumar, Malik, Gami, 2017) during prolonged exposure to temperatures above 50 °C (Kung Jr et al, 2018). NFCs, as long as they are synchronized with the availability of nitrogenous compounds, is the most efficient in increasing milk and meat production as they are substrates for microbial protein synthesis.…”
Section: Discussionmentioning
confidence: 99%